A cross-disciplinary exploration of metadiscourse in experimental research articles - Khedri, Mohsen (2014)
In today’s academic arena, the research article is one of the extensively accomplished communicative genres among members of a particular disciplinary community. Through such a seminal genre, members are able to disseminate their own new knowledge and secure acceptance from addressees. A generic analysis of the research article can enfold issues of different varieties; among them are linguistic features. A crucial part of linguistic features of the research article is shaped through metadiscourse. Metadiscourse is a facet of language which provides a linkage between texts and disciplinary epistemologies, assisting to delineate the rhetorical context by demonstrating some of the readers’ anticipations and expectations. The key principle behind metadiscourse deployment is the view of writing as socially engaging; particularly, it designates writers’ styles whereby they bring themselves into discourses to pronounce their standpoints and commitments to readers. Being so, the current research aimed at exploring the status of metadiscourse in experimental research articles written by scholars belonging to the four disciplines of Applied Linguistics, Psychology, Environmental Engineering and Chemistry. Simply put, this study sought for i) detecting the extent to which metadiscourse markers are incorporated in experimental research articles in the four disciplines; ii) investigating the types of metadiscourse mapped in each rhetorical section (IMRD) of research articles cross-disciplinarily; and iii) finding out different communicative functions fulfiled by the different groups of writers through metadiscourse usage in each of the rhetorical sections (IMRD). To this end, adopting Hyland’s (2005) Interpersonal Model of Metadiscourse and taking a mixed-method of quantitative and qualitative analysis, forty experimental research articles (10 per discipline) sourced from internationally well-known refereed journals were analyzed. Results revealed evident variations across the disciplinary communities regarding both frequency and functional analysis. One salient finding concerns the dominant presence of metadiscourse in both corpora of the soft science disciplines, especially in AL writings. This shows that the style adopted is one that reflects a more writer-responsible style. In contrast, their peers in the fields of EE and Che preferred a reader-responsible approach which imposes on readers to mentally create less obvious linkages between different layers of given information to obtain the message. In terms of writers’ communicative functions of metadiscourse deployment in different rhetorical sections of research articles, more marked cross-disciplinary variations were found. For example, the psychologists, in results and discussion sections, resorted to hedges to reintroduce research purposively/descriptively and to state limitation of their works. These communicative functions were totally absent from the other disciplines. Based on the findings, it can be deduced that metadiscourse use is directly concerned with socio-rhetorical disciplinary norms and conventions established in each particular communities. Results of such an exploratory study could be used by members, especially novice writers in the academic communities concerned to i) make good use of metadiscoursal resources in their writings; ii) broadcast their knowledge through research articles effectively; and iii) familiarize themselves with their respective communities, thus enabling them to gain acceptance from their disciplinary established gatekeepers. The examination of the metadiscourse emphasizes the need to create a reader-based prose which will enhance writing quality that could result in greater opportunities for publication. Much more research could be conducted to seek out the cross-disciplinary differences in rhetorical use in metadiscourse.